Memoirs of a Jewish prisoner of the Gulag - Preigerzon, Zvi (Academic Studies Press, 2022)
Arrest -- Interrogation -- Butyrka Prison -- On the way to Karaganda -- Karaganda -- The Eynikeyt Group -- The people in Karaganda Camp -- In Karaganda Transfer Camp -- On the Way to Inta -- Inta Mineral Prison Camp -- 4th Abez Prison Camp -- Vorkuta -- The 9th Vorkuta Prison Camp -- My fellow Jewish prisoners in the 9th Vorkuta Camp -- Work on coal enrichment : fresh winds -- Release from Vorkuta Prison Camp.